Fundamentals of laser dynamics - Khanin, I͡A. I. (I͡Akov Izrailevich) (Cambridge International Science Pub., 2006)
The book explores the current state of laser dynamics and provides reference data and basic experimental facts for old and new generation lasers. The most frequently used mathematical models are presented. The author discusses the reasons for spontaneous occurrence of pulsation of the intensity of the radiation of solid-state lasers, the influence of the nonstationary nature of parameters and non-linearity of laser elements on the generation characteristics. Special emphasis is placed on the problems of low-frequency dynamics of multimode lasers.